Selected factors that impact low-energy buildings (NZEB) - Pawłowski, Krzysztof; Nakielska, Magdalena (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The Directive 2010/31/EU introduces a new building standard (NZEB) in all member states of the European Union from 1.01.2021. In Poland, a low-energy building has been defined. The design, construction and use of such building is a complex process and requires knowledge of many aspects concerning building materials, general construction, building physics, installations, renewable energy systems and architectural design. Implementation of the current technical requirements in this area encompasses examining many parameters of an entire building but also of its external walls and joints. Defining them according to the applicable legal regulations and relevant standards evokes many questions and uncertainties regarding calculation procedures and interpretation of physical aspects. On the basis of conducted calculations and analyses, the authors have started a discussion on calculation methods in this field, proposing changes in legal regulations and calculation procedures. The paper describes selected factors influencing low-energy buildings: physical parameters of building envelope elements, support of modern ventilation systems, energy performance parameters. The calculation part of the work concerns the analysis of physical parameters of the elements of low-energy building envelope and energy performance parameters of a buildings with consideration of energy saving and thermal insulation criteria. Formation of material systems of external walls and building joints requires taking into account innovative insulation materials and specific parameters of the air inside and outside of a building. The use of professional software for calculations and analyses provides reliable results. Many coherent factors such as: architecture of a building, structural and material solutions of the external walls and their joints (elements of the building envelope), type and efficiency of the ventilation, central heating and hot water systems, use of renewable energy sources, integral management of the building in the field of energy production help to obtain optimal parameters of energy performance of the building and reduce emissions of CO2 to the atmosphere.